The principle of rule of law and independence of the judiciary in Myanmar - Aung, Nge Nge (Journal of Education Culture and Society, 2021)
Aim. This research aims to discuss the importance of the principle of rule of law in protecting the judiciary’s role, especially the independence of constitutional adjudication and its functions. Methods. The study applies the case study approach and comparative method to investigate the constitutional court systems of some countries of the Association of Southeast Asian Nations (ASEAN) and their independence. Results and conclusion. The resultsreveal a lack of the judiciary’s independence, even among the top branches that are trying to implement democracy in Myanmar. The judiciary is under the control of the executive and legislature branches as their members belong to political parties. Moreover, a constitutional court is established with the members who are elected and nominated by the legislature and executive. Sometimes there can be conflicts when constitutional law does not mention the division of powers among governmental organisations like Myanmar, which results from the impractical functions of the Constitutional Tribunal of Myanmar. Cognitive value. This research highlights possible ways to solve the constitutional issues among the three great branches. This initiative is in the interest of Myanmar citizens and citizens of all nations as these are international issues.